Pengembangan Kreativitas Melalui Kegiatan Synectics - Rahmat Aziz (Universitas Islam Indonesia, 2009)
This research used experimental approach which aims to test effectiveness of synectics in developing creative thinking using variables of creative attitude as covariance. The subjects were 48 students of seventh grade of MTs Surya Buana who was divided evenly into experiment and control group. The data was gained through a test of creative thinking and creative attitude scale. Results indicated that synectics proved effective in developing creative thinking.Â Keywords: synectics, creative thinking, creative attitude